2013
DOI: 10.3390/ijms14034684
|View full text |Cite
|
Sign up to set email alerts
|

Irradiated Human Dermal Fibroblasts Are as Efficient as Mouse Fibroblasts as a Feeder Layer to Improve Human Epidermal Cell Culture Lifespan

Abstract: A fibroblast feeder layer is currently the best option for large scale expansion of autologous skin keratinocytes that are to be used for the treatment of severely burned patients. In a clinical context, using a human rather than a mouse feeder layer is desirable to reduce the risk of introducing animal antigens and unknown viruses. This study was designed to evaluate if irradiated human fibroblasts can be used in keratinocyte cultures without affecting their morphological and physiological properties. Keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 54 publications
1
59
0
Order By: Relevance
“…23 Irradiated human dermal fibroblasts provide a suitable human feeder layer that has similar efficiency as mouse fibroblasts for effective expansion of keratinocytes in vitro, but keratinocytes grown without a feeder layer may stop growth after a few passages. 19 Researchers showed that coculture of follicular keratinocytes with dermal fibroblasts treated with mitomycin C supported the proliferation of keratinocytes. They noted that it is easier to handle human fibroblasts than 3T3 cells, and homologous fibroblasts better mimic the physiologic state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Irradiated human dermal fibroblasts provide a suitable human feeder layer that has similar efficiency as mouse fibroblasts for effective expansion of keratinocytes in vitro, but keratinocytes grown without a feeder layer may stop growth after a few passages. 19 Researchers showed that coculture of follicular keratinocytes with dermal fibroblasts treated with mitomycin C supported the proliferation of keratinocytes. They noted that it is easier to handle human fibroblasts than 3T3 cells, and homologous fibroblasts better mimic the physiologic state.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes usually are cultured for 3 to 4 passages for clinical applications. 19 We could culture these cells up to 3 passages. When the keratinocytes could be cultivated after cryopreservation, it was evident that growth of cells with normal morphology was possible on feeder cells in serum-free medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 However, application of 3T3 cells for keratinocyte expansion is associated with the risk of contamination with infections and animal antigens. 18 At present, the focus of research is to discover an optimal protocol for keratinocyte culture.…”
Section: Discussionmentioning
confidence: 99%
“…HDF feeder could be used for iPSCs culture and provides suitable base to support the stem cells. HDF feeder in low passages (P 1-3) could decrease the immune response, easy handling, removing the contamination with animal pathogens, and maintains for long-term periods in the culture (Richards et al 2002;Tecirlioglu et al 2010;Bisson et al 2013;Ghasemi-Dehkordi et al 2014). In recent years, feeder-free culture such as BD Matrigel™ using MEF conditioned medium has been reported to be efficient for culture of stem cells.…”
Section: Introductionmentioning
confidence: 99%